Word coinage communication strategy in learners of English oral interaction - Rushita Ismail; Muriatul Khusmah Musa; Rofiza Aboo Bakar (Journal of English Language Teaching Innovations and Materials (Jeltim), 2021)
Coinage is one of the many creative strategies performed by language learners in instances when they are not able to retrieve the accurate lexical item from their limited linguistic knowledge. It is an issue of interests to language practitioners and learners and little research has been dealt on it. The study explored on the use of coinage strategies among Malaysian language learners in a pair work picture spot- the- difference narration activity. Thirty-two pre-selected items missing from one of the sets were to be identified and the session was video recorded.  From the transcription data, the instances of semantic coinage strategies were found to be  more frequently displayed as compared to grammatical coinage strategy when the learners encountered communication breakdowns. In semantic word coinage strategy, the learners formed lexical items by selecting two different features of the two interlanguage lexical items and combined them as a compound target language item. Grammatical word coinage strategy, on the other hand, was used by creating words which do not exist in the second language (L2) after an application of L2 rule to a L2 word. These communication strategies, in one way or another develop creativity and enhance the process of second language acquisition.